COMPARATIVE CHARACTERISTICS OF MODELS OF STATE SUPPORT FOR NATIONAL ECONOMIES OF THE WORLD IN THE CONTEXT OF THE COVID-19 PANDEMIC - O. A. Lomovtseva; S. Yu. Soboleva; A. V. Sobolev (Вестник университета, 2021)
The article describes economic and social problems of different countries resulting from the spread of the COVID-19 pandemic. The paper defines general and specific characteristics of economic difficulties in developed and developing countries. The authors carry out a preliminary analysis of the economic and social consequences of the coronavirus pandemic for the global economy as a whole. The study presents a comparative description of approaches to the formation of state financial support for businesses and households in developed countries of the European Union, China and Russia. The article identifies two main models of state support – push/pull, shows their differences in the amount of funds, the breadth of coverage of final recipients, the availability of benefits, and the degree of bureaucratization of procedures. The paper reveals the rules and procedures for providing state events to support businesses and entrepreneurs on the Russian market, and also uncovers shortcomings that significantly affected the economic situation of agents. The authors describe the consequences of lockdown for the economies of various countries. The study conducts a screen analysis of health systems and their mobilization response to the spread of coronavirus infection. The paper draws conclusions about the advantages of proactive social support for the population and business, the need to increase its targeting and the spread of effective practices in the future.